Pemahaman Masyarakat Kecamatan Medan Tembung dalam Digitalisasi Zakat: Understanding of the Medan Tembung District Community in Digitalizing Zakat - Ali Amzah; Yenni Samri Juliati Nasution (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
This research aims to determine the understanding of the people of Medan Tembung District in digitalizing Zakat directly to the community. The research approach used is a qualitative approach using primary data sources through interviews with the people of Medan Tembung District regarding an in-depth understanding of Zakat Digitalization. Several data collection methods used in this research are Observation, Interview, and Literature Study. The results of the analysis show that the people of Medan Tembung sub-district do not fully understand the zakat digitization system, there are some people who understand the digitalization of zakat, and some even cannot understand the digitalization of zakat. What influences the people of Medan Tembung District are adaptation, mindset, age, level of education, economic income and social environment.